Deep venous thrombosis prophylaxis in oral and maxillofacial surgery: A Brazilian survey - Marcelo S Monnazzi; Luis A Passeri; Mario FR Gabrielli; Eduardo Hochuli-Vieira; Marisa AC Gabrielli; V A Pereira Filho (Wolters Kluwer Medknow Publications, 2012)
Background : Deep venous thrombosis (DVP) is a frequent disease. Prophylaxis is the best means to reduce its incidence, for lowering morbidity and mortality rates and treatment costs caused by its complications. Objective : To evaluate the knowledge and use of any kind of DVT prophylaxis by Brazilian Oral and Maxillofacial surgeons. Materials and Methods : A questionnaire was sent to all Oral and Maxillofacial surgeons associated to the Brazilian College of Oral and Maxillofacial Surgeons that have a valid e-mail address. The data retrieved was evaluated and tabulated. Results : Of the 1100 questionnaires sent, only 4% were retrieved. The 42 retrieved were included in the study. Twenty six of the surgeons do not use any kind of deep venous thrombosis (DVT) prophylaxis, 11 use mechanical means as elastic compressive stockings or pneumatic compressive devices for prophylaxis, and 5 uses low-molecular weight heparins (LMWH) as the choice for prophylaxis. Conclusion : The data collected, despite the low rate of participation (4%) by the surgeons, shows that this subject still does not receive proper attention. Whereas other medical specialties make routine use of prophylactic means maybe the maxillofacial surgeons lack concern on that matter.